Anti-Bullying Program Development: Building a Safe and Supportive School Environment for Adolescents - M. Rusdi; Radi Udin Alfian Sangaji; Dedi Gunawan Saputra; Eko Prasetyo; Andro Ruben Runtu (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2024)
Bullying significantly impacts students' mental, social, and academic well-being, particularly in schools. This study analyzes bullying and proposes an anti-bullying program through a descriptive literature review. By reviewing scientific journals and research reports, it identifies the prevalence, causes, impacts, and effectiveness of existing programs. Findings indicate that 30-40% of students experience physical, verbal, or cyberbullying. Contributing factors include power imbalances, limited teacher involvement, and weak family support. Bullying impacts include anxiety, depression, low self-confidence, and declining academic performance.Programs emphasizing empathy and cooperation with active student participation are more effective than teacher-centered approaches. This study introduces a novel framework combining technology for reporting and monitoring cases with a community-based strategy involving students, teachers, and parents. This approach is essential to address challenges like cyberbullying in the digital era. By promoting collaboration among all school stakeholders, the program aims to create a safe and inclusive environment for students. The study provides evidence-based insights and practical solutions for developing more effective anti-bullying strategies, adaptable for schools in Indonesia and beyond.